2000
DOI: 10.1074/jbc.275.6.4323
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Ca2+ Pump Isoform 3f Is Weakly Stimulated by Calmodulin

Abstract: Isoform 3f of the plasma membrane Ca2؉ pump is a major isoform of this pump in rat skeletal muscle. It has an unusual structure, with a short carboxyl-terminal regulatory region of only 33 residues when compared with the 77 to 124 residues found in the other isoforms. Also, whereas the regulatory regions of the other isoforms, downstream of the alternative splice, consist of two homologous groups, the sequence of 3f is not related to either group. A synthetic peptide representing the calmodulin binding domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Unfortunately, the information presently available on functional differences among isoforms is fragmentary at best. The problem is further exacerbated by the existence, next to the four basic gene products of the pump, of numerous alternatively spliced variants, which also display tissue-specific ex- pression and which in some cases may be even more abundantly expressed than the unspliced versions (12,13). Although the most extensively studied splice variants involve splice site C in the C-terminal cytosolic unit, splice variants involving site A, located immediately downstream of the domain that mediates the regulatory action of acidic phospholipids in the Nterminal half of the pump would also be however potentially interesting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the information presently available on functional differences among isoforms is fragmentary at best. The problem is further exacerbated by the existence, next to the four basic gene products of the pump, of numerous alternatively spliced variants, which also display tissue-specific ex- pression and which in some cases may be even more abundantly expressed than the unspliced versions (12,13). Although the most extensively studied splice variants involve splice site C in the C-terminal cytosolic unit, splice variants involving site A, located immediately downstream of the domain that mediates the regulatory action of acidic phospholipids in the Nterminal half of the pump would also be however potentially interesting.…”
Section: Discussionmentioning
confidence: 99%
“…A C-terminally spliced variant of PMCA3, termed 3f (or 3CVI), in which a short insert leads to the loss of most of the C-terminal portion downstream of the calmodulin-binding domain (11) has also been analyzed. This isoform, which has been detected in skeletal muscle and to a lesser extent in brain, has very weak calmodulin affinity (12,13). Unfortunately, these studies were performed on isolated pump domains or on membrane preparations from overexpressing mammalian or insect cells in which possible physiological pump regulators may have become lost.…”
mentioning
confidence: 99%
“…Modeled concentration of each species as a function of time for dissociation of C28W(1b) from CaM-AF488. Sequences of the CaM binding domains for different isoforms of PMCA (37,38). The first 18 residues (underlined) are identical for all isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in the ten Cterminal residues of these isoforms are sufficient to dramatically alter their CaM binding affinities (36,37). For instance, a recent study reported dissociation constants of CaM binding to C28W peptides from isoforms 3f and 2b that were nearly two orders of magnitude apart (38), and these differences must originate in the sequence differences in the C-terminal portions of the respective CaM binding regions. Thus, the differences in the kinetics reported for isoforms 1b and 4b must be due to the amino-acid sequence differences (only three of them, shown in lower case in Figure 6) in the C-terminal 10 residues of the CaM binding domains of isoforms 1b and 4b.…”
Section: Relationship To Isoform 4bmentioning
confidence: 99%
“…A cell that utilizes PMCA to respond rapidly to a Ca 2ϩ spike requires an isoform that has a high basal activity, such as isoform 3f in heart muscle (2), and/or one that is activated rapidly by calmodulin, such as isoform 2a in inner ear hair cells. In contrast, a cell that requires a sustained Ca 2ϩ signal may utilize isoforms with low basal activity and slow activation by Ca 2ϩ -calmodulin, such as isoform 4b in Jurkat T lymphocytes (3).…”
mentioning
confidence: 99%